(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Media is an important institution in a Democracy. Media plays the role of watchdog in any society. The Study focuses on changing standards and perspectives of Indian media. We look at four case studies too understand these changes. The roles of press during emergency, media during Bofors scandal are the two case studies in the late seventies and eighties in India. They highlight the integrity of the press leading to political changes in the polity. Two case studies from the present period are the role of press during corona crisis and the Sushant Singh Rajput case. They highlight the falling standards of journalism and threats that emanate from the same to Democracy. Sustainable ethics is a concept that means that media has to survive in the market by following ethical practices and be force for positive political and social change. It is to be seen how media survives this dark phase in Indian Journalism.